Analisis Kecerdasan Emosional Karakter Utama dalam Thao's You've Reached Sam - Ni Nyoman Ayu Sanjiwani; I Gusti Ayu Gde Sosiowati; Ni Ketut Widhiarcani Matradewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article aimed to analyze the aspects of emotional intelligence experienced by the main character in You’ve Reached Sam novel written by Thao. To analyze the emotional intelligence aspects, this study used the Theory of Emotional Intelligence conducted by Goleman (1998). Furthermore, the data is collected from the utterances in the novel that presents the aspects of emotional intelligence. This study used the descriptive qualitative method, while the documentation and note-taking technique is also applied in order to collect the data. The finding of this study shows that the main character in the novel experienced the five aspects of emotional intelligence. Thus, the emotional intelligence contributed in solving the main character’s problem throughout the story.